Photobacterium damselae subsp. damselae, an Emerging Pathogen Affecting New Cultured Marine Fish Species in Southern Spain - Labella, A.; Berbel, C.; Manchado, M.; Castro, D.; Borrego, J.J. (IntechOpen, 2011)
None